Analyses of the factors influencing the accuracy of three-dimensional ultrasound in comparison with cone-beam CT in image-guided radiotherapy for prostate cancer with or without pelvic lymph node irradiation - Zhou, Sha (Radiat Oncol, 2019)
BACKGROUND: Three-dimensional ultrasound (3DUS) is an attractive option in image-guided radiotherapy (IGRT) for prostate cancer (PCa) patients. However, the potential factors influencing the accuracy of 3DUS in comparison with cone-beam CT (CBCT) in IGRT for PCa patients haven’t been clearly identified. METHODS: The differences between US/US and CBCT/CT registrations were analyzed over 586 and 580 sessions for 24 and 25 PCa patients treated with or without pelvic lymph node irradiation, respectively. The clinical factors that may influence registration differences were also evaluated. RESULTS: The average discrepancies between US/US and CBCT/CT registrations were − 0.28 ± 5.28 mm, − 0.16 ± 3.48 mm, and − 0.47 ± 4.31 mm in the superior-inferior (SI), left-right (LR), and anterior-posterior (AP) directions, respectively. The discrepancies were respectively less than 5 mm longitudinally, laterally, and vertically in 64.4 and 70.1%, 84.9 and 89.2%, and 75.9 and 79.1% of the patients treated with or without pelvic lymph node irradiation, respectively. The registration differences were significantly smaller at least in one direction in patients younger than 70 years, without pelvic lymph node irradiation, guided by transperineal ultrasonography and had a bladder volume smaller than 300 mL. CONCLUSIONS: Age, irradiated regions, 3DUS modality, and bladder volume are important factors that may influence the differences between US/US and CBCT/CT registrations. 3DUS guidance is more feasible for younger PCa patients with a better control of bladder volume during the treatment and those who did not undergo pelvic lymph node irradiation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13014-019-1217-0) contains supplementary material, which is available to authorized users.